Inclusion of Anti-COVID-19 Related Research Highlights into the Classroom: Why, What and How? - Du, Yu'an; Tian, Junjie; Weng, Guo-Ming (CV. AFDIFAL MAJU BERKAH, 2024)
Bringing recent research highlights into the classroom has drawn an intense amount of interest because it can show students what are being discovered, especially those anti-COVID-19 works. Therefore, we aim to study the feasibility and share the thoughts on the relevant innovation in education during the pandemic of COVID-19. To do so, we first examine participants’ (consisting of bachelor, master and PhD students at different universities) attitudes of towards the inclusion of anti-COVID-19 related research highlights into the classroom via the survey questionnaires. It is found that students mostly preferred such an innovative move. We then feature multiple anti-COVID-19 research highlights, ranging from the anti-fog materials, new inhalation treatment approach, antiviral 2D materials, efficiency enhancement of mask materials, rapid detection methods to vaccine development. Next, we elaborate the class design such as contents, objectives, difficulty level and learning outcomes with two specific examples. Lastly, suggestions for better implementation of including anti-COVID-19 related research highlights into the classroom are provided. The findings of this study can help universities and teachers to further improve the class design, thereby creating strong anti-COVID-19 related theory-practice linkages for students.